Current status of Citrus tristeza virus in Lebanon - Choueiri E. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
This paper summarizes the field status of citrus tristeza virus (CTV) in Lebanon. Based on the first virus survey conducted in citrus commercial groves and nurseries in autumn of 1996, CTV was reported officially in Lebanon with an overall infection rate of 1.43 percent. Another survey was undertaken between 1998 and 2000 in Mount Lebanon in addition to the adoption of four experimental plots in the South to assess the CTV incidence. CTV was only detected in the South with an increased infection rate from 1.2 to 3.8 percent in plot II, and from 2 to 5 percent in plot III whereas the CTV infection rate in plot I was stable (1.1 percent) with no concomitant infection in plot IV. The vectors Aphis gossypii and Aphis citricola were identified whereas Toxoptera citricidus, the most efficient CTV vector, was not encountered. With the aim to establishing a citrus mother block for the production of plant certified material, another field survey was carried out between 2003 and 2004 in the South and North of Lebanon close to LARI stations and CTV was found only in the South. Interestingly, no evidence of the disease was observed in the CTV-infected trees as ascertained by repeated observations in the field. Further work and preventive measures should be applied to secure the future of the citrus industry in Lebanon.